ANALISIS EMPIRIS MULTIMEDIA INTERAKTIF MATERI HUKUM NEWTON TENTANG GERAK SEBAGAI MEDIA PEMBELAJARAN FISIKA DI SMA KELAS X - Munafiah Munafiah; Azhar Azhar; Muhammad Nasir (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to description the results of empirical analysis of interactive multimedia newton’s law of motion material as a media of physics learning in the first year of senior high school consisting of empirical validity and reliability. This is survey type. The subjects of this study are the first year students of SMAN 2 Rambah Hilir consisting of 15 male students and 15 female students. The data was collected by scoring of multimedia score given to the respondent through questionnaire, then the data is analyzed by validity test applying product moment correlation technique and reliability test applying cronbach's alpha technique. Based on the data analysis, the validity of the scores of all respondents to the interactive multimedia is greater than the rkritis and reliability score assessment of all respondents to the interactive multimedia has a value of cronbach's alpha greater than 0.7. Based on the results that the interactive multimedia of newton's law of motion material is stated valid and reliable, so interactive multimedia can be used as a media of physics learning in the first year of senior high school.Keywords: Empirical Analysis, Interactive Multimedia, Newton’s Law of Motion Material